Respuesta :

Answer:

The answer to your question is:

x = 3

y = 6

z = - 1

Step-by-step explanation:

                                              - x - y - z = - 8      (I)

                                         - 4x + 4y + 5z = 7     (II)

                                                   2x + 2z = 4     (III)

                                                   2z = 4 - 2x

                                                     z = 2 - x       (IIIA)

Substitute IIIA in I

- x - y - (2 - x) = - 8      - x - y - 2 + x = -8      - y - 2 = -8      - y = -8 + 2   y = 6

Substitute IIIA and y in II

                                         - 4x + 4(6) + 5(2 - x) = 7  

                                           -4x + 24 + 10 - 5x = 7

                                          -9x = 7 -34

                                          -9x = -27

                                          x = 3

Substitute x in IIIA

                                                z = 2 - 3

                                                z = - 1